2017
DOI: 10.1063/1.4982912
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stress induced interface states in Al2O3/InGaAs metal-oxide-semiconductor capacitors

Abstract: Implementation of high-k dielectrics on InGaAs for CMOS technology requires capabilities to predict long-time degradation and the impact of process changes on degradation processes. In this work, the degradation under constant voltage stress of metal gate/Al 2 O 3 /InGaAs stacks is studied for n-type and p-type As 2 passivated InGaAs substrates. The results show that the degradation for both positive bias and negative bias did not produce Al 2 O 3 oxide traps, while the distribution of interface states increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The positive shift of the threshold voltage at a positive bias stress indicates electron trapping from the semiconductor to the oxide and passivation of positive charge. 53 From the figure, it is observed that sample A [3:3] has the lowest shift of 86.2 mV while sample D [1:9] has the highest (282.5 eV). Thus, this stress-induced charge trapping maintains a linearity with the Hf content with a higher amount of Hf causing a higher quantity of charges to be trapped.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive shift of the threshold voltage at a positive bias stress indicates electron trapping from the semiconductor to the oxide and passivation of positive charge. 53 From the figure, it is observed that sample A [3:3] has the lowest shift of 86.2 mV while sample D [1:9] has the highest (282.5 eV). Thus, this stress-induced charge trapping maintains a linearity with the Hf content with a higher amount of Hf causing a higher quantity of charges to be trapped.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The threshold voltage shift (Δ V TH ) after 2000 s of CVS at 1.5 V for all samples is illustrated in Figure c, where Δ V TH is the difference of the threshold voltage of a fresh device and stressed device. The positive shift of the threshold voltage at a positive bias stress indicates electron trapping from the semiconductor to the oxide and passivation of positive charge . From the figure, it is observed that sample A [3:3] has the lowest shift of 86.2 mV while sample D [1:9] has the highest (282.5 eV).…”
Section: Resultsmentioning
confidence: 99%